2012
DOI: 10.3892/mmr.2012.1149
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of seven myogenesis-related genes in extraocular muscles of patients with concomitant strabismus

Abstract: Abstract. Hyperplasia or hypoplasia of muscles gradually leads to strabismus. Myogenesis-related genes are involved in extraocular muscle development, including myogenic differentiation 1 (MYOD1), myogenin (MYOG), retinoblastoma 1 (RB1), cyclin-dependent kinase inhibitor 1A (P21), cyclin-dependent kinase inhibitor 1C (P57), insulin-like growth factor 1 (IGF1) and muscle creatine kinase (MCK). This study evaluated the expression of the above seven myogenesis-related genes by realtime quantitative RT-PCR in 18 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…32 Downregulation of PAX7 is consistent with alteration of myogenesis-related genes such as MYOD1 , myosins, and filament-related muscle proteins (see proteomics, microarray data, 21 and qPCR data 22 ).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…32 Downregulation of PAX7 is consistent with alteration of myogenesis-related genes such as MYOD1 , myosins, and filament-related muscle proteins (see proteomics, microarray data, 21 and qPCR data 22 ).…”
Section: Resultsmentioning
confidence: 83%
“…We found that the large majority of relevant ligands, receptors, and transcription factors were expressed in the tendon compartment (Table 2), while a smaller number were primarily expressed in muscle, along with genes known to be expressed in muscle, such as MUSK , PAX7 , and MYOD1 . 22,32 Interestingly, several members of the same family of genes were expressed primarily in either tendon or muscle, but very few were equally distributed in both, indicating specialized compartment-specific functions of distinct members (e.g., MMP2 in tendon, MMP9 in muscle). In addition, some ligands were expressed in one compartment while their receptors were expressed in the other compartment, suggesting that ligands produced in one compartment (e.g., muscle) signal to receptors in the other compartment (e.g., tendon).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations